Math, asked by SushmaAnupamaEkka, 6 months ago


Determine the value of x in
( \frac{2}{3} ) {}^{3}  \times ( \frac{2}{3} ) {}^{ - 6}  = ( \frac{2}{3} ) {}^{2x - 1}

Answers

Answered by patelshrina
1

Step-by-step explanation:

( \frac{2}{3} ) ^{3}  \times ( \frac{2}{3} ) ^{ - 6}  = ( \frac{2}{3}) ^{2x - 1}

since the base of all exponent is same

==> 3+ (-6) = 2x -1

==> -3 +1 = 2x

==> -2 = 2x

==>

 - 1 = x

Answered by tathagatabanerjee68
0

Answer:

3/9 is the answerrrrrrrr brooooo

Similar questions